2001
DOI: 10.1097/00001199-200106000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PET Findings in Patients with Posttraumatic Anosmia

Abstract: Findings strongly suggest that posttraumatic anosmia is closely associated with hypometabolism in the orbitofrontal cortex and the medial prefrontal cortex. The results also underscore the importance of posttraumatic anosmia as a clinical sign of orbitofrontal damage, as has been shown previously with neuroSPECT (single photon emission computed tomography).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Neuropsychiatric disorders that feature impulsivity (i.e., Borderline Personality disorder, Tourette's syndrome, traumatic brain injury) are associated with PFC dysfunction, as demonstrated by results of several of neuroimaging studies (44)(45)(46). Similarly, reports from electrophysiological studies in adolescents with conduct problems and adults with alcoholism have linked inhibitory control impairment and PFC dysfunction.…”
Section: The Neurobiological Basis Of Inhibitory Control: Role Of Thementioning
confidence: 97%
“…Neuropsychiatric disorders that feature impulsivity (i.e., Borderline Personality disorder, Tourette's syndrome, traumatic brain injury) are associated with PFC dysfunction, as demonstrated by results of several of neuroimaging studies (44)(45)(46). Similarly, reports from electrophysiological studies in adolescents with conduct problems and adults with alcoholism have linked inhibitory control impairment and PFC dysfunction.…”
Section: The Neurobiological Basis Of Inhibitory Control: Role Of Thementioning
confidence: 97%
“…Other imaging modalities such as single-photon emission computed tomography (SPECT) and positron-emission tomography (PET) have been investigated in patients with olfactory dysfunction with promising findings [62][63][64]. However as they were not used in patients whose loss was specifically posttraumatic loss the diagnostic role of these tests remains to be elucidated.…”
Section: Neuroimagingmentioning
confidence: 99%
“…When using SPECT to investigate brain activity in posttraumatic anosmia, researchers found reduced perfusion in frontal, left parietal and left temporal regions [15]. Another study confirmed reduced metabolism in the median prefrontal cortex and the orbitofrontal cortex of patients with posttraumatic anosmia [16]. Moreover, a recent functional imaging study done with patients with obsessive compulsive disorder showed the importance of the orbitofrontal cortex and the pre-frontal cortex in odour perception, with results supporting connections between the orbitofrontal cortex and the olfactory sensory system in a clinical population [17].…”
Section: Introductionmentioning
confidence: 95%